Diagnóstico del potencial de la biomasa vertida en el botadero de basura de Latacunga, en relación con el volúmen y energía asociada en el año 2013. Y propuesta de un sistema eficiente para la generación de enrgía eléctrica. - Mena Venegas, Iván Oswaldo (2015)
The controlled garbage dump of Municipal GAD from Latacunga Canton, Cotopaxi province, in operation since 1981, has not implemented any biogas collection system, all solid wastes are disposed therein in a controlled manner, but the generation of such gases are emitted directly into the environment. The objective of this research project is to determine the amount of biogas that can be obtained; presenting an alternative to take advantage of flammable characteristics of biogas in order to produce electricity by using internal combustion engines coupled a generator to it. Currently at the garbage dump arrive on average 103,90 tons / day of urban solid waste which implies that are available annually 37,923.50 tons, with the indicated amount of waste can be obtained biogas 411 ⁄ of biogas. Given that 1 biogas recovered from garbage dump contains 50% methane , approximately whose calorific value is of 10,8 ⁄ , the beginning of electricity production would be subordinated to the allocation of resources by the Municipal GAD or sponsorship thereof and this could run from 2016, to operate three generators of 280 kW would be used for 2024 and its generating facilities would be completed over two 280 kW generator, all power generation is able to produce; it would be delivered to the distribution network to the electrical enterprise and thus the decomposition of solid waste would be transformed into clean energy. Moreover, with the capture of biogas produced in the garbage dump will be achieved considerably to reduce the environment contamination and with these actions get lessen the effects of warming overall that is caused when methane goes directly to the atmosphere.